Apelin in epiretinal membranes of patients with proliferative diabetic retinopathy - Lu, Qiang (Molecular Vision, 2014)
PURPOSE: Formation of epiretinal membranes (ERMs) in the posterior fundus results in visual impairment. ERMs have been associated with numerous clinical conditions, including proliferative diabetic retinopathy (PDR), a neovascular disease. Apelin has been identified as a novel angiogenesis contributor. The aim of this study was to investigate the correlation between apelin and ERMs after PDR. METHODS: ERM samples were obtained by vitrectomy from 12 subjects with PDR (aged 57±6 years; duration of diabetes 16±7 years), and 12 subjects with idiopathic ERM (aged 68±5 years). The samples were processed for immunohistochemistry and reverse transcription–PCR (RT–PCR). We also analyzed samples from patients with PDR who received an intravitreal injection of bevacizumab (IVB) before vitrectomy. RESULTS: The mRNA expression of apelin was significantly higher in the PDR ERMs than in the idiopathic ERMs. Accordingly, immunohistochemical analysis revealed strong expression of apelin in all eight PDR ERMs without IVB, and was double-labeled with glial fibrillary acidic protein antibody (GFAP), platelet endothelial cell adhesion molecule-1 (CD31), cytokeratin (CK) and vascular endothelial growth factor (VEGF) but not with fibronectin. They were mainly located in the adventitia. In contrast, the expression of apelin was lower in the PDR ERMs after IVB and the idiopathic ERMs. CONCLUSIONS: The results showed that apelin was involved in the formation of ERMs and promoted the formation of adventitia, including glial, endothelial, and RPE cells. Bevacizumab blocked the expression of apelin and regressed gliosis and angiogenesis.